Application-based Simulation on the Digital Trunking Radio Communication System to Predict the Area Coverage - Arief Goeritno; Nesia Andriana; Indriya Indriya; Ika Setyawibawa; Dwi Suhartono (Universitas Ahmad Dahlan, 2022)
A radio communication system (RCS) based on digital trunking of the digital mobile radio (DMR) type of Tier-III with any of the brands is installed, consisting of mobile radio devices, portable radio devices, repeater devices, devices antenna, and power supply device. The technical specifications for these types of equipment have been approved by institution-owned. This paper describes a radio communication system infrastructure based on a digital trunking RCS for predicting the area coverage for independent or private use. The research contributions of this study include (a) predicting the signal of area coverage of the repeater and radio devices and (b) observing results of communication performance on the DMR Tier-III Trunking radio communication system. Research methods for achieving research objectives, including five main parameters are required connectivity, the DMR application for predicting radio signal area coverage of the repeater system, and observation of the communication performance. Tuning on the repeater system include five conditions, while on radio equipment includes four conditions. Prediction and observation of the coverage area based on seven parameters as input. The simulation results are in the form of a screenshot with an area coverage of 140.938 kilometers. The observation of communication performance through dummy loads in the form of providing types of artificial condition calls. In general, after the research objectives are obtained, it is expected that the system is well connected.